METHODS OF SPEECH DEVELOPMENT IN THE PROCESS OF PRESCHOOL CHILDREN’S ENVIRONMENTAL LEARNING - Shaymanova Yulduz Toshniyazovna (International Engineering Journal For Research & Development, 2022)
The article discusses important aspects of speech culture. The formation of the culture of speech in preschool children and the attitude to the methods of the educator's skill. The role of cognition and perception in the formation of speech in preschool children is based on examples.